Treatment of young patients with HNF1A mutations (HNF1A-MODY) - Raile, Klemens; Schober, E.; Konrad, K.; Thon, A.; Grulich-Henn, Jürgen; Meissner, T.; Wölfle, J.; Scheuing, N.; Holl, R. W. (Diabetic medicine, 2015)
Aim Children and adolescents with a molecular diagnosis of HNF1A-MODY should be treated with oral sulfonylurea according to current International Society for Pediatric and Adolescent Diabetes (ISPAD) guidelines. Methods We surveyed the German-Austrian DPV database of 50 043 people and included 114 patients with a confirmed molecular-genetic diagnosis of HNF1A mutation and diabetes onset at below age 18 years. We analysed hypoglycaemic episodes, metabolic control (HbA1c) and other clinical variables according to treatment groups. Results People with HNF1A-MODY were included and analysed according to treatment with insulin alone (n = 34), sulfonylurea (n = 30), meglitinides (n = 22) or lifestyle (n = 28). In those receiving any drug treatment (n = 86), severe hypoglycaemia did not occur with meglitinide and was highest (at 3.6 events per 100 patient-years) with insulin. HbA1c was highest with insulin treatment (insulin = 58 mmol/mol, 7.5%; sulfonylurea = 55 mmol/mol, 7.2%; meglitinides = 52 mmol/mol, 6.9%; P = 0.008), whereas weight (BMI SD score), serum lipids and blood pressure were not different. Conclusions Of note, 40% of people with HNF1A-MODY and medical treatment were receiving insulin alone and thus were not being treated in line with up-to-date International Society for Pediatric and Adolescent Diabetes/International Diabetes Federation guidelines, despite insulin treatment being associated with worse metabolic control and the risk of hypoglycaemia. The unlicensed use of oral drugs in patients below age 18 years and adherence by both doctors and patients to the initial insulin treatment might contribute to this finding.
Gesehen am 10.06.2020